CACING TANAH DARI BIOTOP HUTAN, BELUKAR, DAN KEBUN TEH DI KAWASAN GAMBUNG - JAWA BARAT - MS., Nurdin
Earthworm populations of the forest, scrub and tea Plantation biotopes of the area of Research Institute for Tea and Chinchona Gambung Estate, have been studied during the period of AugustNovember 1981. The three biotopes varied in their species diversity and vegetational cover. In the forest Metaphire javanica, Metaphire capensis and two other unidentified Metaphire (Metaphire sp.l and Metaphire sp.2) were found, in the scrub, Metaphire sp.l and Pontoscolex corethrurus whereas in the tea plantation, Metaphire sp.l and Metaphire sp.2. The population densities of the earthworm ranged between 7.122.2 per m2 (1.028.69 g dry weight per m2), 1.18.9 per m2 (0.161.39 g dry weight per m2) and 1.11.39 per m2 (0.080.81 g dry weight per m2) in the forest, the scrub and the tea plantation, respectively. The C/N ratio, pH and the organic content of the soil of the forest, the scrub and the tea plantation were relatively similar, whereas the total, the calsium and magnesium exchangeable ions values of the forest were higher than those of the scrub and the tea plantation. The total, calsium and magnesium exchangeable ions were h higher on the plots with a relatively high earthworm population density. Experiments carried out in the scrub biotope showed that spraying-with Cobox (0.05%) decreased the earthwormA population, while spraying with Kelthane did not. Laboratory experiment showed that spraying the soil with Cobox, Kelthane and Lebaycid with a concentration of 0.05% did not decrease earthworm population densities. Experiments carried out in the scrub biotope showed that digging of the soil decreased the population density of the earthworm. Pontoscolex corethrurus reared under laboratory conditions showed a sigmoid growth curve according to [FORMULA, click on the file to see the formula] (W=weight in mg; t=time in day). The rate of growth of the earthworm was relatively higher fed on powdered grass than on powdered Lantana camara, Schima wallichii and Thea sinensis leaves, respectively. Daily production of castings of Pontoscolex corethrurus tends to correlate with its body weight according to the equation Wc=7.117 W0.746 (Wc=casting weight per day; W=body weight).